Synthesis of oligocarbonate diols from a "green monomer" - dimethyl carbonate - as soft segments for poly(urethane-urea) elastomers - Tomczyk, K.; Parzuchowski, P. G.; Kozakiewicz, J.; Przybylski, J.; Rokicki, G. (Polimery, 2010)
Results from the investigation of a two-step synthesis of oligocarbonate diols from a "green monomer" - dimethyl carbonate (DMC) are presented and discussed. In the first step 1,6-hexanediol or 1,10-decanediol was reacted with DMC to obtain bis(methylcarbonate)hexamethylene (1h) or bis(methylcarbonate)decamethylene (1d), respectively which were further reacted in the next step with appropriate diol at a intended molar ratio to obtain the final product. The solvent - 1,4-dioxane - served as a suppressant of the evaporation of both the diol and low molecular weight oligomers, while facilitating the removal of residual amount of methanol and full conversion of methylcarbonate groups. This method allows for the synthesis of oligocarbonate diols without ether linkages containing exclusively terminal hydroxyl groups and of desired molecular weights. It was shown that such oligomerols can be applied for the preparation of poly(urethane-urea) elastomers. The obtained elastomers based on oligocarbonate diols of molecular weights ranging from 1700 to 2700 exhibited very good mechanical properties.